Data sources for rescuing the rich heritage of Mediterranean historical surface climate data. (12th April 2013) - Brunet, M.; Jones, P. D.; Jourdain, S.; Efthymiadis, D.; Kerrouche, M.; Boroneant, C.
<x xml:space="preserve">Abstract</x> Availability of long‐term and high‐quality instrumental climate records is still insufficient and the rich heritage of meteorological surface observations is largely underexploited in many parts of the world. This is particularly striking over the Greater Mediterranean region (GMR), where meteorological observations have been taken since the 18th century at some locations. The lack of high quality and long series here is despite this region being regarded as a climate change hot spot. This article mainly assesses relevant sources containing Mediterranean historical climate data and metadata either from online repositories worldwide or physical archives, with the emphasis here on the rich holdings kept at French archives. A particular case study is the data rescue (DARE) program undertaken by the Algerian National Meteorological Service, as well as some of the past and ongoing projects and initiatives aimed at enhancing climate data availability and accessibility over the GMR. Our findings point to the high potential for undertaking DARE activities over the GMR and the need for bringing longer and higher quality climate time series to support a diverse number of scientific and technical assessments and policies.